(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) was implemented and came into force on Groundhog Day, 2006. it had been the primary act of its kind within the world wherein an economic safety net is provided to around 23rd of the population through a right to figure . the size on which it’s been provided is simply mindboggling, engaging around 1 10th of the entire world population. it had been second during a series of right based policies Government of India has unrolled within the past decade. It’s clear that the program is not any bright side but have several clouts related to it.